Synthesis and pharmacological evaluation of some quinoline derivatives as potential cognition enhancers - Piplani, Poonam; Rani, Anita; Saihgal, Ruchika; Sharma, Meenakshi (Arzneimittelforschung, 2011)
The present paper describes the synthesis of a series of substituted 6-amino (1 a–c) and 8-aminoquinoline derivatives (2b–c) and the evaluation of their ability to prevent the memory decline using a behavioural model, i. e. the elevated plus maze test. The effect of the candidate drugs on the activity of acetylcholinesterase was studied using the enzyme source from the mouse brain. The structures of the synthesized compounds were confirmed by UV, IR, 1H-NMR and elemental analysis. The 6-aminoquinoline derivative [6-(4-pyridyl)methylaminoquinoline] (1 c) oxalate showed maximum % retention (50% at 5 mg/kg and 75% at 10 mg/kg) in the elevated plus maze test and maximum% inhibition (71% at 25 µM) of AChE on biochemical evaluation.
Keywords: Acetycholinesterase; 6-Aminoquinolines; 8-Aminoquinolines; Cogniton enhancers; Elevated plus maze; Quinolines